Harnessing nanoprodrugs to enhance cancer immunotherapy: overcoming barriers to precision treatment - Yunfan Lin; Pei Lin; Xu Chen; Xinyuan Zhao; Li Cui (Materials Today Bio)
Nanoprodrugs, leveraging advanced nanoparticle-based delivery systems, represent a promising strategy to enhance the efficacy of immunotherapy in cancer treatment. These systems offer precise tumor targeting, controlled drug release, and the potential to modulate the immune microenvironment, addressing several limitations of conventional therapeutic approaches. This review systematically evaluates the role of nanoprodrugs in improving immunotherapy outcomes, focusing on their ability to overcome challenges such as poor bioavailability, systemic toxicity, and limited tumor specificity. We also discuss the key advantages of these systems, including their ability to co-deliver immune checkpoint inhibitors and other immunomodulatory agents, potentially enabling more synergistic and effective treatment strategies. Despite their promise, several challenges remain, including achieving precise control over drug release, integrating multiple stimulus-responsive mechanisms, addressing tumor heterogeneity, and overcoming barriers to clinical translation. The review concludes with a perspective on future directions, emphasizing the need for further optimization of nanomaterial design, improved delivery strategies, and solutions to the complexities of the tumor microenvironment to maximize the clinical impact of nanoprodrugs in cancer immunotherapy.